Keterasingan dan Ingatan Traumatik Tokoh dalam Film Rumah untuk Alie: Implikasi untuk Pembelajaran Bahasa Indonesia - Elvyana Eka Aryanti; Anas Ahmadi (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study analyzes the representation of alienation and traumatic memories in Herwin Novianto's film Rumah untuk Alie (2025), utilizing approaches from literary psychology, Erich Fromm's theory of alienation, Cathy Caruth's theory of trauma, and Roland Barthes's film semiotics. The analysis was conducted not only to map the psychological dynamics of the main character but also to identify the relevance of these findings for Indonesian Language and Literature learning. The film demonstrates how family trauma and experiences of alienation shape the character's behavior, communication patterns, and emotional development—all of which are important aspects in character education, film appreciation learning, and strengthening students' emotional literacy. The results show that Alie's alienation is visualized through a cold domestic space, visual compositions that separate the characters, and minimal emotional contact. Meanwhile, traumatic memories are evoked through the use of non-linear flashbacks, repetitive sounds, and symbols such as cracks in family photographs. These findings have significant implications for Indonesian Language and Literature education, particularly in developing film-based learning, implementing trauma-sensitive pedagogy, and strengthening student empathy through character analysis and sociocultural context.